Presentation of a Professional Competency Model for Employees of Bank Mellat, Islamic Republic of Iran, with a Qualitative and Quantitative Approach - Kianezhadtejenaki, Seyed Mahmoud; Jafari Kalarijani, Seyed Ahmad; Mehrara, Asadollah; Shakki, Mohammad Hasan (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The present study aims to present a professional competency model for employees of Bank Mellat, Islamic Republic of Iran, based on human and social development. Methodology: In this research, the participants in the qualitative section included all experts and specialists in the field of public administration and managers and heads of Bank Mellat, Islamic Republic of Iran, with a scientific background related to human resources and a history of working as a manager or consultant in the banking industry in 2022, totaling 15 individuals. The statistical population in the quantitative section included all managers and employees of Bank Mellat, Islamic Republic of Iran, in 2023-2024. In the quantitative phase, the sample size was determined using Cochran’s formula, resulting in 384 individuals, who were selected through cluster random sampling. The findings from the qualitative phase were analyzed using MAXQDA software. Findings: From the analysis of 15 interviews, a total of 236 initial codes were extracted. After analyzing the interview texts, 41 basic themes and 15 organizing themes were identified. The results of the quantitative section showed that the dimensions of professional competencies for Bank Mellat employees included: the organizational competency dimension, with a factor loading of 0.873, ranked first; the social competency dimension, with a factor loading of 0.823, ranked second; the leadership competency dimension, with a factor loading of 0.746, ranked third; and the individual competencies and self-development dimension, with a factor loading of 0.685, ranked fourth. Conclusion: The model highlights fostering continuous learning, effective communication, and innovation through training and feedback. Future research should explore broader applications across diverse organizations to validate and refine these findings.